ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP KAPITALISASI PASAR DAN RETURN SAHAM PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA - Mundaryatiningsih, Sari
Measurement of firm's performance is the most important thing that investor should did to define investment. In this case, investor and creditor need a good measurement that provide good valuation to value firm's performance exactly. This research's objective is to analysis the influence of financial performance: accounting profit, Return On Investment (ROI), Economic Value Added (EVA), and Market Value Added (MVA) to market capitalization and stock return that measured by abnormal stock return. This event study research employed 48 firm sample that included in LQ 45 Index and have fulfilled sample selection criterion in 1999 - 2002 period. This research used multiple linear regression analysis and used F-test, t-test, also classical assumption of regression. The result of this research shows that there is influence between EVA and MVA to the market capitalization and stock return. Further, there is evidence that EVA and MVA influence market capitalization in positive way, EVA influence abnormal stock return in negative way, and MVA influence abnormal stock return in positive way. The result of this research prove that EVA and MVA beat domination of financial traditional measure accounting profit and ROI in their influence to the market capitalization and stock return. And there is evidence that MVA have domination to the EVA in its influence to the market capitalization and stock return